Numerical analysis of underground tunnels subjected to surface blast loads (Fracture and Structural Integrity, 2020)
The increased terrorist attacks on important public structures and utilities have raised the vital necessity for the investigation of performance of structures under blast loads to improve the design and enhance the behavior of structures subjected to such threats. In this study, 3-D ﬁnite element analysis is used to study the effect of surface explosions on the response of RC bored tunnels. The soil behavior is modelled using Drucker-Prager Cap model. Two types of soil are investigated, and the blast load is considered through various weights of TNT explosive charges at heights of 0.50 m and 1.0 m from ground surface. To study the effect of horizontal standoff distance, six different horizontal distances are considered. The results show that the soil type has a significance effect on tunnel response due to surface blasts. Also the weight and the location of charge have a great effect on the safety of the tunnel. Finally, a parametric study is established to define the borders of the restricted area around the tunnel location to be safe.
Keywords: Finite element analysis; TNT; RC tunnel; Drucker Prager Cap Model